Contesting the humanitarian regime in political emergencies: International NGO policies and practices in Sri Lanka & Afghanistan, 1990-2010 - Aneja, U (2013)
The legal humanitarian regime, set out in the Geneva Conventions and Additional Protocols, strives to alleviate human suffering through the provision of emergency goods and services, such as food supplies, water, temporary shelter, and medical treatment. This thesis examines how international non-government organizations (INGOs) contribute to the contestation of this regime in political emergencies, the effects of this contestation, and the factors driving INGO contestation. The thesis develops an analytical framework for understanding the nature and functioning of the legal humanitarian regime, and argues that INGO contestation occurs through the two processes of regime interpretation and regime implementation. It then goes on to identify the substantive content and effects of contestation, and the factors driving INGO contestation of the regime, through a detailed study of the policies and practices of CARE, Médecins Sans Frontiers, Oxfam, and World Vision, in Afghanistan and Sri Lanka, from 1990-2010. The thesis argues that contestation has constitutive effects, as it re-defines the meaning of the formal humanitarian regime, and the underlying rules and norms that specify the regime’s function, scope, and operating principles. Contestation also has causal effects, as it can make INGOs participants in the conflict, eroding thereby the basis on which they negotiate access and their ability to respond to humanitarian needs, and the security of their staff. It has also facilitated the subordination of humanitarian assistance by donor states and combatants to their political and security objectives. INGO identity - expressed in terms of the constituent rules and norms that define INGO membership, their mandate and goals, and the manner in which they distinguish themselves from other actors - is argued to be a necessary factor for explaining INGO contestation. The focus on identity highlights the agency of INGOs in shaping the humanitarian regime and demonstrates that INGOs are not simply at the mercy of more powerful actors or external constraints.